Differences in the effect of adolescents’ strategies for expressing academic emotions on academic emotions and peer acceptance in competitive and cooperative situations - Liu, Ying; Chai, Xiaoyun; Sang, Biao; Zhang, Shaohua (Frontiers in Psychology, 2024)
Two studies were conducted to explore the differences in the effect of adolescents' strategies for expressing academic emotions. In Study 1 a total of 65 adolescents participated in the study of the relationship between academic emotions and strategies for expressing them in competitive and cooperative situations. In Study 2 a total of 113 adolescents participated in the study of the relationship between the strategies and peer acceptance in competitive and cooperative situations. The results showed that the relationship between academic emotions and strategies for expressing them in competitive and cooperative situations was situation stable while the relationship between the strategies and peer acceptance was situation specific. Furthermore, emotional expression may be more adaptive when experiencing positive academic emotions. When adolescents experience negative academic emotions, expressing them is more adaptive from the perspective of their own academic emotional experience; whereas suppressing them is more adaptive from the perspective of peer acceptance. These findings (a) clarify how to use more adaptive strategies for emotional expression in various situations and (b) serve as a guide for helping adolescents use strategies to express emotions flexibly according to the situation.